Historical background of itch - Weisshaar, Elke; Eckart, Wolfgang U.; Bernhard, Jeffrey D. (Pharmacology of itch, 2015)
Itch as a disease, and especially as a symptom, was the object of medical and scientific curiosity for centuries. The reluctance of historians to focus on the history of itch relates to its nature as a subjective symptom. After all, how can historians have known what itch really felt like in previous centuries? Since the establishment of dermatology as an independent discipline of medicine in the middle of the nineteenth century, itch has become a subject of investigation in its own right. This chapter summarises research we conducted on the medical history of itch in ancient medicine and up through the twentieth century.
Gesehen am 06.07.2020